Existence of deconstructivism in the architecture of the historical environment - Astanin Miсhael (Theory and practice of design, 2022)
The article analyzes the problem of coexistence of multi-style structures. Architectural structures built in the early twentieth century within the historical boundaries of the centers of European capitals are studied. The realized projects of world-famous architects Bernard Chumi, Zahi Hadid, Jean Nouvel, Renzo Piano are considered. The influence of structures on the historical environment and the social reaction caused by these structures has been revealed. The urban landscape is considered and analyzed for the presence of deconstructivist structures in the most ancient capital cities: Athens, Rome, Paris and London. Characteristic features, general and distinctive features of these constructions are fixed. At the beginning of the twentieth century, the question of the coexistence and interaction of ancient and modern architectural structures, the importance and meaning of preserving the existing architectural complexes of historical buildings were actively discussed and provoked many conflicting opinions. Throughout the twentieth and twenty-first centuries, issues have been and are the subject of heated debate and debate. In the urban aspect, this area is studied by experts and scientists who have given their recommendations for solving such a complex issue. For almost a hundred years, urban forums have been adopting international regulations and rules for the construction of historic cities. The article analyzes the architectural structures that appeared during the reign of motifs of deconstructivism in the world architectural style and the environment in which they appeared, which they began to influence and which affects them in reverse order. The landscape and mentality of urban dictates dictate the conditions for the introduction of avant-garde architecture, which can be perceived as antiphonal, but the iconic nature of its images obsessively attracts attention. The development of technology and innovation act as a driving force of architecture, and the aesthetics of significant volumes are solved in complex sculptural forms. Foreign and domestic researchers have studied the processes of preservation of historic cities in the general conditions of development and their evolutionary transformation. One of the International Charters, adopted in Washington (Washington Charter, 1987), states the following about historic cities. It is allowed to introduce elements of modern character into the existing historically formed fabric of the urban ensemble, provided that they do not disturb the harmony of the ensemble. Such elements can enrich the artistic image of the ensemble. Thus, there are no objections to the latest construction in historic cities. Questions of the form and image of buildings remain open. In London, «The Shard» skyscraper became the tallest building in the city. Located near the transport hub, the skyscraper with its vertical volume puts a symbolic exclamation mark over the horizontal cluster of railways, logically and compositionally completing this strip of trains, converting its energy in the vertical direction. One can agree with the theorists of affordance, ie theories of visual perception, who claim that an extremely bold decision is implemented quite professionally. The buildings of architects Frank Gehry and Jean Nouvel in Paris are built in diametrically opposed places relative to the center of the capital and are located in a park area. Active and dynamic forms attract attention first of all. They contrast sharply with the background of the environment and are the most sculptural in plastic, more outrageous and extravagant than their Athenian and Roman style relatives. Unlike the London Skyscraper, in Rome the museum building is spread out horizontally and does not violate the high-altitude boundaries of the conditional “blue stripe”. One and a half hundred meters of the facade on the side of Via Luigi Poletti stretch two deaf concrete strips. Massive volumes without any window openings give the impression of an engineering structure such as a retaining wall or dam. The flat, deaf volumes of the museum contrast sharply with the historic 19th-century building across the street. The building of the museum in Athens is almost similar in design to the Roman museum, but its facades are not deaf, but composed of rhythmic rows of transparent panels and screens. Like the Roman Museum of MAXXI, the Athenian Museum is located in the center of the quarter. The physical size of the building is larger than the Parthenon, located nearby on Mount Acropolis. The height of the museum is calculated in such a way that the surrounding active terrain does not allow the building to attract attention. Ascetic, as for deconstructivism, the object of the Athenian Museum is hidden behind trees and low-rise buildings of different eras. The principles of the formation of objects of deconstructivism in the historical environment have much in common, but in each case there are individual differences. The buildings are quite large in size and affect the environment, but the environment in turn creates a background on which the special qualities of the deconstructivist style are revealed. The buildings received personal nicknames from the locals: in Athens — “The Сareer”, in Rome — “The Spaghetti”, in Paris — “The Rock”, in London — “The Shard”, which proves that deconstructivism mimics volumes and forms that are created naturally. By 2020, in the so-called pre-COVID times, the times of revival of tourist movements, the need to build sculptures or, as Jean Nouvel called them, “illusory attractions” was extremely relevant.